Seamount effect on circulation and distribution of ocean taxa in the vicinity of La Pérouse, a shallow seamount in the southwestern Indian Ocean. (June 2020) - Marsac, Francis; Annasawmy, Pavanee; Noyon, Margaux; Demarcq, Hervé; Soria, Marc; Rabearisoa, Njaratiana; Bach, Pascal; Cherel, Yves; Grelet, Jacques; Romanov, Evgeny
Abstract: The La Pérouse seamount (60 m depth) has so far been poorly studied despite it being a short distance (160 km) from Réunion Island. As part of the MADRidge project, a multidisciplinary cruise was conducted to evaluate the effect of this shallow seamount on the local hydrology and ecology. Current measurements, temperature and chlorophyll- a profiles, and mesozooplankton and micronekton samples were collected between the summit and 35 km away. Micronekton data were supplemented with stomach content of pelagic top predators as well as fisheries statistics from the domestic longline fleet operating from Réunion. Vertical current profiles revealed distinct patterns between the offshore and seamount-flanked stations, giving evidence of topographical induced flow instabilities, notably on its leeward side (west) relative to the east flank. Distinct patterns in temperature and chlorophyll- a vertical profiles suggest the formation of convergent and divergent circulation cells as a result of the irregular and crescent-like summit topography. Spatial differences in zooplankton abundance were detected with higher biovolumes on the leeward flank. The overall acoustic backscatter for micronekton over the summit was weaker than offshore, but highly concentrated in the upper layer. Albacore tuna and swordfish dominate the longline catch west of Réunion, seemingly in association with a deep (900 m) topographic feature. Yet the largest catch is not directly associated with La Pérouse which would be too shallow for top predators to aggregate around in the long term. Enhanced levels of phytoplankton or zooplankton enrichment at La Pérouse were not demonstrated in this study, nor was there notable diversity of micronekton species. This might explain the relatively limited importance of this seamount to the tuna fisheries in this region.